An Exploration of the Islamic Legal Principle of Maslaha al-Mursala as a Panacea to the Clamouring for Resource Control and Restructuring in Nigeria - Alade, Owoyemi Samuwilu; Oriowo, Adeoye Tawaliu (NIU Journal of Humanities, 2023)
During the administration of President Muhammadu Buhari (2015-2023), the clamour for resource control and restructuring threatened the corporate existence of Nigeria as a united and indivisible country. It seems that the 1999 Nigerian Constitution has failed to address some fundamental issues that are germane to the existence of the Federal Republic of Nigeria. The purpose of the study is to examine the Islamic legal principle of maṣlaḥa al-murṣalaḥ (unstated common good/public interest) and explain how it can be applied to amend the Nigerian Constitution as a panacea to the clamouring for resource control and restructuring in Nigeria. The methodology adopted in this study is qualitative research based on the existing literature on resource control and restructuring. While advocating socio-economic and religious restructuring of Nigeria, the study recommends, based on the principle of maslaha al-mursalaha , that 1999 Constitution should be amended to accommodate laws that will address issues on resource control and restructuring. The paper recommends that states should be allowed to take 80% of the resources found in their respective states or regions while 20% of the resources should be allocated to the Federal Government.  There should be a review in the Federal Allocation/Fiscal Policy among the three tiers of government. Federal Government should also promote justice, fairness and equity (which Islam preaches) among the federating units and continue to wage ‘war’ against corruption, insurgency, militancy, kidnapping and other crimes (which Islam forbids) that are threatening the cooperate existence of Nigeria. Keywords: Resource control, Restructuring Nigeria, clamouring, maslaha al-mursalah , maqasid shari’ah